Librarians job satisfaction / Noor Izzati Mohd Radzi, Nurul Nadia Karim and Wan Nurul Syahida Wan Kamaruddin Mukri - Mohd Radzi, Noor Izzati; Karim, Nurul Nadia; Wan Kamaruddin Mukri, Wan Nurul Syahida (Faculty of Information Management, 2015)
This article discusses about the job satisfaction among the librarian towards their job who are serving the national library, public library, academic library and special library. The eight factors of job satisfaction were working environment, ICT infrastructure, the nature of work, personal growth, salaries, and annual increment. This article also discussed about the challenges of job satisfaction; ICT development, inadequate funding and gender biased. So, with the list of problems that has been discussed, this article states the strategies for increasing the motivational among worker to fulfill the satisfaction in the job.